Upward nominal wage rigidity - Guimarães, Paulo; Martins, Fernando; Portugal, Pedro (Bonn, 2017)
"In Portugal, as in many other countries in continental Europe, the collective wage agreements between trade unions and employer associations that define wage floors for specific job titles are systematically extended to the whole industry. This means that many firms are obliged to increase the wages of their workforce in order to comply with the newly-agreed bargained wages. With some trepidation, we call this phenomenon upward nominal wage rigidity, in close symmetry with the Keynesian notion of downward nominal wage rigidity. In this paper we provide evidence that firms that are more heavily affected by the change in the bargained wage floors decrease their hiring rates and, more importantly, significantly increase their separation rates. As a complement to our analysis, we suggest the estimation of a measure that attempts to disentangle the strength of internal and external wage conditions. Based on this measure we show that firms whose wages are more influenced by external wages exhibit much lower net job creation rates."